2004
DOI: 10.1063/1.1794353
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of high-quality strain-relaxed thin SiGe layers on ion-implanted Si substrates

Abstract: We fabricated high-quality strain-relaxed thin SiGe layers by Ar ion implantation into Si substrates before epitaxial growth. The surface of 100-nm-thick Si0.8Ge0.2 layers, the relaxation ratio of which was more than 80%, was found to be very smooth, with a rms roughness of 0.34 nm. Cross-sectional transmission electron microscopy analysis confirmed that strain-relieving dislocations were effectively generated due to the ion-implantation-induced defects and confined in the vicinity of the heterointerface, resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…Actually, relaxation ratios of SiGe estimated from the peak values are 90% and 50% in the implanted and unimplanted regions, respectively. This observed difference in the relaxation ratio is very comparable to our previous work [6] where implanted and unimplanted Si wafers were separately prepared and SiGe layers were grown on each wafer. It is remarkable that the almost relaxed and strained (partially relaxed) regions are simultaneously formed in one continuous SiGe layer.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Actually, relaxation ratios of SiGe estimated from the peak values are 90% and 50% in the implanted and unimplanted regions, respectively. This observed difference in the relaxation ratio is very comparable to our previous work [6] where implanted and unimplanted Si wafers were separately prepared and SiGe layers were grown on each wafer. It is remarkable that the almost relaxed and strained (partially relaxed) regions are simultaneously formed in one continuous SiGe layer.…”
Section: Resultssupporting
confidence: 88%
“…In this study, as a novel strain controlling technique we propose selective ion-implantation technique, which is able to provide benefits of both local and global strains. So far, the SiGe buffer layer fabrication method utilizing ion implantation has been developed by several groups [2][3][4][5][6][7] and it has been demonstrated that ion-implantation-induced defects acting as dislocation sources are able to markedly enhance a degree of strain-relaxation of thin SiGe layers. Here, we applied this technique to local controlling of strain by means of introducing the defects selectively.…”
Section: Introductionmentioning
confidence: 99%
“…We implanted Ar ions into the Si substrates before the MBE growth of the SiGe and succeeded in forming highly relaxed SiGe thin film [15 -18]. Not only were we able to get a relaxed SiGe thin film, but also the crystallinity of the SiGe was high when a post annealing process was carried out [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…However, this growth method has critical problems, such as the SiGe layer thickness becomes very large to reduce threading dislocation density, and surface roughening of SiGe layers becomes huge. In the previous works [20,21], we reported that thin Si 0.8 Ge 0.2 relaxed layers with smooth surface, which is comparable to that realized by chemical mechanical polishing (CMP), were fabricated by the ion implantation method where implantation with Ar + , Si + or Ge + ion was carried out into Si substrate. In this study, we fabricated high-quality thin SiGe relaxed layer with much higher Ge composition by the ion implantation method and formed strained Ge p-channel modulation doped structures.…”
Section: Introductionmentioning
confidence: 99%